A comparative study using different resins to determine thorium isotopes - Mychelle Munyck Linhares Rosa; Maria Helena Tirollo Taddei; Luan Teixeira Vieira Cheberle; Paulo Sérgio Cardoso Silva; Vera Akiko Maihara (Brazilian Journal of Radiation Sciences)
Thorium is a naturally occurring radioactive element that is widely distributed in the crust of the Earth. This element is very common in mineral formations in regions with high levels of natural radioactivity, therefore, its determination in environmental samples is important. Thorium isotopes (228Th, 230Th, and 232Th) were determined in a reference material, the IAEA Soil 327 sample, to validate the two methods, these isotopes were also analyzed in two groups of food samples, employing these different resins. The initial preparation with acid dissolution is the same to both, in the first is used anion exchange resin (DOWEX 1x2) and electrodeposition in silver planchets. And in the second method is used a specific chromatographic resin (TEVA) and cerium fluoride microprecipitation. At the end both analysis are quantified by alpha spectrometry. The two methods the results obtained were satisfactory for the reference material used, with relative error of less than 4% for 228Th, 230Th, and 232Th. The analysis of variance for samples foods analyzed seen to be no significant difference between the methods used for thorium isotopes determination. The main differences found between methods were spectrums resolutions, time and cost of analysis.